Assessment of community disaster resilience the case of flood and landside-prone communities in Buhi, Camarines Sur - Magayanes, Laarni M. (School of Urban and Regional Planning, University of the Philippines Diliman, 2024)
The Philippines is already used to being affected by numerous natural disasters. Many strong typhoons and other natural disasters have already caused disastrous effects on the lives and properties of the Filipinos. The exposure and susceptibility of the country to natural and human-induced hazards, caused efforts and initiatives to strengthen communities and people's capacities and resilience to disasters.